2018
DOI: 10.1371/journal.pone.0198351
|View full text |Cite
|
Sign up to set email alerts
|

Impact of OGT deregulation on EZH2 target genes FOXA1 and FOXC1 expression in breast cancer cells

Abstract: Enhancer of zest homolog 2 (EZH2) is a histone methyltransferase which plays a crucial role in cancer progression by regulation of genes involved in cellular processes such as proliferation, invasion and self-renewal. Activity and biological function of EZH2 are regulated by posttranslational modifications. It is suggested that EZH2 stability may be regulated by O-GlcNAc transferase (OGT), which is an enzyme catalyzing the addition of GlcNAc moieties to target proteins. In this study, we determined the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…SIRT6 is a kind of deacetylase that regulates the transcription of its target genes by interacting with various transcription factors 39 . Accumulating studies found that the acetylation of EZH2 enhances its capacity in regulating FOXC1 28 , 40 . To determine whether MDL-811 could regulate EZH2 acetylation under our experimental conditions, we assessed the levels of acetylated EZH2 by immunoprecipitation.…”
Section: Resultsmentioning
confidence: 99%
“…SIRT6 is a kind of deacetylase that regulates the transcription of its target genes by interacting with various transcription factors 39 . Accumulating studies found that the acetylation of EZH2 enhances its capacity in regulating FOXC1 28 , 40 . To determine whether MDL-811 could regulate EZH2 acetylation under our experimental conditions, we assessed the levels of acetylated EZH2 by immunoprecipitation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, FOXA1 and FOXA2, both of which play an important role in α-cell glucagon biosynthesis and secretion ( 28 ), are O-GlcNAc modified by OGT in cancer cells, and this modification is important for the stability of the protein ( 29 ). Moreover, OGT has been shown to directly bind to the promoter of FOXA1 to regulate its expression levels ( 30 ). In the current study, we show that FOXA2 mRNA and protein levels were reduced in α-cell line with OGT inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, EZH2 O-GlcNAcylation does not affect PRC2 assembly but occurs at the N-terminal region, including the S73, S76, S84, S87 and T313 sites, which may regulate the stability of the isolated EZH2, while O-GlcNAcylation of EZH2 at S729 is required for the methyltransferase activity of PRC2 to catalyse H3K27me2/3 [ 154 , 155 ]. Another study revealed that O-GlcNAcylation of EZH2 affects its binding to the promoter regions of FOXA1/C1 (Forkhead box protein A1/C1), suggesting that EZH2 O-GlcNAcylation might affect the targeting of PRC2 to chromatin [ 156 ]. Overall, these observations suggest that O-GlcNAcylation of EZH2 may regulate the catalytic activity and genomic targeting of PRC2.…”
Section: Ptms Fine-tune Prc2 In Multiple Processesmentioning
confidence: 99%